GraphITA : Selected papers from the Workshop on Synthesis, Characterization and Technological Exploitation of Graphene and 2D Materials Beyond Graphene - Morandi, Vittorio; Ottaviano, Luca (Springer International Publishing : Imprint: Springer, 2017)
This book presents selected papers from the fourth edition of the GraphX conference series, GraphITA 2015. Its content range from fundamentals to applications of graphene and other 2D material such as silicene, BN and MoS2. The newest technological challenges in the field are described in this book, written by worldwide known scientists working with 2D materials. The chapter 'Morphing Graphene-Based Systems for Applications: Perspectives from Simulations' is published open access under a CC BY 4.0 license.
Keywords: Materials science.; Condensed matter.; Nanotechnology.; Structural materials.; Optical materials.; Electronic materials.; elektronické knihy; electronic books